2016
DOI: 10.1371/journal.pone.0161819
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Hypoxaemia Developed at Sea-Level Influences Responses to Exercise at Moderate Altitude

Abstract: PurposeThe aim of this study was to investigate the impact of exercise-induced hypoxaemia (EIH) developed at sea-level on exercise responses at moderate acute altitude.MethodsTwenty three subjects divided in three groups of individuals: highly trained with EIH (n = 7); highly trained without EIH (n = 8) and untrained participants (n = 8) performed two maximal incremental tests at sea-level and at 2,150 m. Haemoglobin O2 saturation (SpO2), heart rate, oxygen uptake (VO2) and several ventilatory parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 38 publications
(55 reference statements)
4
32
0
Order By: Relevance
“…Previous research using pulse oximetry indicated that %SaO 2 values fall in the range between 84% and 93% [6,8,13,30,31]. Similar changes were observed in our study with the % SaO 2 decreased in the range between 85% and 92% during incremental exercise test.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Previous research using pulse oximetry indicated that %SaO 2 values fall in the range between 84% and 93% [6,8,13,30,31]. Similar changes were observed in our study with the % SaO 2 decreased in the range between 85% and 92% during incremental exercise test.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have shown a greater drop in the SaO 2 at both maximal and sub-maximal exercise during treadmill running compared with ergometer cycling [16,33]. In the present study, we used incremental treadmill exercise while some studies used incremental exercise on cycle ergometers that have displayed higher [13][14][15][16][17]. Differences of exercise modality and protocol types used may help to explain the differences in SaO 2 measured.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Given that the ALT test was truly performed at altitude (and not at SL under hyperbaric conditions), logistic constraints prevented us from using the same equipment for exercise sessions and measurements at both SL and at ALT. As has also been described in the literature, VO 2 , power output and SpO 2 during exercise were significantly lower at ALT than at SL (Gore et al 1996, Gaston et al 2016). While no difference was observed for the VE during exercise between SL and ALT, VE/VCO2 was higher and PetCO 2 was lower at ALT when compared to SLsuggesting excessive hyperventilation and poor ventilatory efficiency (Mollard et al 2007).…”
Section: Discussionsupporting
confidence: 83%
“…As altitude increases, EIAD is exacerbated in all individuals 22 . There is also significant interindividual variability in the severity of EIAD experienced during exercise, even within groups of similarly trained athletes 12 26 . Therefore, assuming EIAD and tHb are independent, EIAD may influence the relationship between tHb and VO 2 max.…”
Section: Introductionmentioning
confidence: 99%